Hypogenesis of right hepatic lobe in a laparoscopic cholecystectomy for acute gallstone cholecystitis: A case report - Fujimoto, Yuka (Intractable Rare Dis Res, 2019)
Hypogenesis or agenesis of right hepatic lobe is a rare abnormality and is generally associated with gallbladder and biliary tract abnormalities. Cases of biliary injury following cholecystectomy have been reported in patients with agenesis of right hepatic lobe because the anatomical anomalies complicate the surgical approach. We report a case of laparoscopic cholecystectomy in a patient with hypogenesis of right hepatic lobe. A 92-year-old male patient was admitted to our hospital with fever and right lower abdominal pain with suspected acute appendicitis. Abdominal computed tomography revealed gallstones with acute cholecystitis and hypogenesis of right hepatic lobe. He underwent laparoscopic cholecystectomy with the left semilateral decubitus position. The patient's postoperative course was uneventful. In conclusions, some patients with liver lobe hypoplasia do not present with the typical symptoms of acute cholecystitis due to dislocation of the gallbladder. The left semilateral decubitus position with modified placement of port sites is useful for laparoscopic cholecystectomy in patients with hypogenesis of right hepatic lobe.